Gastrointestinal stromal tumors (GISTs): A case report - Shuvekcha Thapa; Kunwar, Sarjan; Pandey, Bijay; Shrestha, Deependra Man (Journal of Gandaki Medical College-Nepal, 2026)
Gastrointestinal stromal tumors (GISTs) are rare malignant tumors, rarely found in jejunum. Diagnosis mainly relies on histopathological examination and immunohistochemistry. Management typically includes surgery and chemotherapy. Herein, we present a case of an older adult female with abdominal pain and a palpable lump and managed by small bowel resection and adjuvant imatinib therapy. The excised tumor showed positive immunoreactivity for CD117, DOG-1 and SMA. This case report highlights the importance of considering GISTs in abdominal masses and the role of CT imaging and Immunohistochemistry in diagnosis and management.